2018
DOI: 10.3899/jrheum.170344
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Safety and Efficacy of Subcutaneous Abatacept in Patients with Rheumatoid Arthritis: 5-year Results from a Phase IIIb Trial

Abstract: Objective.To assess 5-year safety, tolerability, and efficacy of subcutaneous (SC) abatacept (ABA) in methotrexate (MTX)-refractory patients with rheumatoid arthritis (RA).Methods.The Abatacept Comparison of sub[QU]cutaneous versus intravenous in Inadequate Responders to methotrexatE (ACQUIRE) phase IIIb, randomized, double-dummy, multinational trial compared efficacy and safety of SC and intravenous (IV) ABA in patients with RA. In the initial 6-month double-blind (DB) period, patients received IV or SC ABA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…An integrated analysis of safety data from the double-blind and open-label periods of 5 clinical trials including a total of 1879 RA refractory patients with 4214.6 patient-years of exposure, showed that treatment with SC ABA was associated with a low incidence of serious infections, malignancies, autoimmune events, and injection-site reactions [ 39 ]. Our data regarding the safety profile of SC ABA are similar to the 5-year extension period of the ACQUIRE study [ 40 ], and RWD from the ACTION study [ 13 ]. In addition, similar results have been found in Argentine patients with respect to the security profile when exposed to IV ABA administration [ 20 ].…”
Section: Discussionmentioning
confidence: 62%
“…An integrated analysis of safety data from the double-blind and open-label periods of 5 clinical trials including a total of 1879 RA refractory patients with 4214.6 patient-years of exposure, showed that treatment with SC ABA was associated with a low incidence of serious infections, malignancies, autoimmune events, and injection-site reactions [ 39 ]. Our data regarding the safety profile of SC ABA are similar to the 5-year extension period of the ACQUIRE study [ 40 ], and RWD from the ACTION study [ 13 ]. In addition, similar results have been found in Argentine patients with respect to the security profile when exposed to IV ABA administration [ 20 ].…”
Section: Discussionmentioning
confidence: 62%
“…In support of the consistencies noted above, safety data from LTE studies and meta-analyses of biologic and targeted synthetic DMARDs are comparable with those reported for tofacitinib. Considering discontinuation from biologic DMARDs, 62% of patients discontinued by year 10 of treatment in an LTE study of adalimumab (23% due to AEs and 12% due to lack of efficacy/disease progression) [27]; and 31% of patients discontinued by year 5 in an LTE study of subcutaneous abatacept (31% due to AEs and 7% due to lack of efficacy) [28]. Considering safety events of special interest, previous LTE studies have reported IRs for serious infections of 3.1 and 1.7 events for adalimumab (across 10 years of treatment) and subcutaneous abatacept (across 5 years of treatment), respectively [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Considering discontinuation from biologic DMARDs, 62% of patients discontinued by year 10 of treatment in an LTE study of adalimumab (23% due to AEs and 12% due to lack of efficacy/disease progression) [27]; and 31% of patients discontinued by year 5 in an LTE study of subcutaneous abatacept (31% due to AEs and 7% due to lack of efficacy) [28]. Considering safety events of special interest, previous LTE studies have reported IRs for serious infections of 3.1 and 1.7 events for adalimumab (across 10 years of treatment) and subcutaneous abatacept (across 5 years of treatment), respectively [27, 28]. In the integrated analysis of safety data for baricitinib, event IRs were reported for serious infections (3.0), herpes zoster (3.3), tuberculosis (0.1), MACE (0.5), DVT (0.4), PE (0.2), malignancies excluding NMSC (0.8), lymphoma (0.08), NMSC (0.4), and gastrointestinal perforation (0.04) [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…5 The long-term safety of SC abatacept showed a low incidence of serious infections, malignancies, autoimmune events, and injectionsite reactions. 6,12,[17][18][19][20][21][22][23][24][25][26] Due to the limited budget, we had only four vials of SC abatacept and to decrease the risk of side effects, we extended the intervals between doses using the frequency of initial IV abatacept doses, biweekly for three doses (i.e. a dose at weeks zero, two, and four) and the fourth dose administered at week eight.…”
Section: Discussionmentioning
confidence: 99%